From 2016 coup to bonapartism - Andrade, Everaldo de Oliveira (2020)
With 2016’s impeachment as a starting point, the article discusses perspectives and elements announced for the future government of Jair Bolsonaro, characterizing them with the concept of Bonapartism. It makes this discussion considering the ongoing transformations in the world economy in the context of structural crisis, as well as pointing out the limitations of “weak reformism” as a government policy. It also emphasize the importance of the resumption of full democracy, which requires overcoming Bonapartism and the fascist threat by building new democratic institutions and popular mobilization.